MATRIX METHODS AND THEORETICAL STUDIES OF RODS FOR VIBRO-CREEP - Буратинський, Андрій (Modern engineering and innovative technologies, 2025)
The paper presents theoretical studies of reinforced concrete rods with consideration of concrete vibro-creep. Various theories of vibro-creep and their application to the analysis of the stress-strain state of rods are considered. Particular attention i